Neuroplastic Changes Following Social Cognition Training in Schizophrenia: A Systematic Review - Campos, Carlos (2017)
Social cognitive impairment is a key feature of schizophrenia and social cognition training (SCT) is a promising tool to address these deficits. Neurobiological dysfunction in schizophrenia has been widely researched, but neuronal changes induced by SCT have been scarcely explored. This review aims to assess the neuroplastic effects of SCT in patients with schizophrenia spectrum disorders. PubMed and Web of Science databases were searched for clinical trials testing the effects of SCT in functional and structural brain measurements of adult patients with schizophrenia or schizoaffective disorders. A total of 11 studies were included: five used fMRI, two used EEG and ERP, one used ERP only, two used MEG and one study used MRI. Data extracting and processing regarding sociodemographic and clinical variables, intervention characteristics, neuroimaging procedures, neuroplastic findings, effect sizes and study quality criteria was completed by two raters. Results indicate a wide range of structural and functional changes in numerous regions and circuits of the social brain, including early perceptual areas, the limbic system and prefrontal regions. Despite the small number of trials currently available, evidence suggests that SCT is associated with neuroplastic changes in the social brain and concomitant improvements in social cognitive performance. There is a lack of extensive knowledge about the neural mechanisms that underlie social cognitive enhancement after treatment, but the reported findings may shed light on the neural substrates of social cognitive impairment in schizophrenia and how improved treatment procedures can be developed and applied.